Innovative use of brick waste for eco-friendly treatment of indigo dye house wastewater: An approach towards waste to resource - Hafiz Usama Imad; Rasool Bux Mahar; Ashfaque Ahmed Pathan; Shayan Shehzad; Muhammad Osama; Faiz Naeem (Mehran University Research Journal of Engineering and Technology)
The textile industry is the backbone of Pakistan’s economy, holding a share of 57% in total exports of Pakistan but also possessing several environmental challenges due to the discharge of highly contaminated wastewater. On the other hand, construction and demolition waste is another threat to the environment because of its massive quantity and large area requirement for its disposal. This study explores the use of waste bricks as a sustainable medium to treat textile wastewater. Waste bricks, sourced from construction debris in Hyderabad, were crushed, cleaned, and used in the treatment system. Composite samples of textile effluent were collected from a textile factory in Nooriabad, Sindh, and treated in a brick column treatment system over 14 days. Key parameters such as pH, turbidity, total dissolved solids (TDS), total suspended solids (TSS), hardness, chloride concentration, chemical oxygen demand (COD), dye concentration, electrical conductivity (EC), and total solids (TS) were monitored using standard methods. The results revealed that the waste brick filtration system effectively reduced various pollutants within four2 days and improved further, with significant decreases in COD (94%), dye concentration (99%) , and turbidity (91%) after 14 days, indicating that waste bricks can be a green alternative for wastewater treatment, promoting the concept of “using waste to treat waste” and contributing to environmental sustainability.